Práticas de estudo on-line de universitários: cognição e subjetivação de jovens professores - Rodrigues, Denise Costa (2018)
Formal education and internet are important factors for the constitution of subjects. They display different languages and ways of control, as formal education values deep and recognizably valuable knowledge, while the internet offers superficial information at high speed. Or at least this is the perspective spread by most educators, who conceive the internet as an agent with diverging purposes from schools and universities, and which, therefore, should be kept away from such institutions – unless in situations in which the internet is invited to make a quick visit to the classroom, aiming to redirect the youth’s attention to the course contents. Keep the internet outside educational institutions has not been an easy task. (MIRANDA, 2007; SIBILIA, 2012.). It is worth it to ask if it is a productive task at all, considering that learning is a process of inventive problematization (KASTRUP, 2008). Indeed, the considerable part of the mentioned youth is being currently prepared to play the role of teachers in the Brazilian basic education classrooms. The object of this investigation is the online study practices employed by undergraduate students majoring in Pedagogy and Literacy by the Federal University of Ceará, Brazil. For this study, all intentional learning acts which engaged some online tool were considered online study practices. Recognition and invention processes fostered by online study practices performed by people engaged in formal teacher training were analyzed according to the cartography method for qualitative research as it is presented by Passos, Kastrup e Tedesco (2014). The mapping of learning networks constituted by online study practices of young teachers showed that the college students mix traditional study practices with online ones, building a relationship of complementarity among them. We notice the need for further investigation on the effects of such studying practices on the subjectivation of the young teachers.